Management of Natural Tourism Objects in Minahasa Regency North Sulawesi Province - Lengkong, Florence D. J.; Londa, Very Y.; Palar, Novie R. A.; Tulusan, Femmy M.G. (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
Minahasa Regency has the potential of natural resources to become a tourist attraction. This potential has been managed by the government but the management pattern is the same as that carried out by other regions that rely more on natural conditions. This research was conducted to find the form and pattern of managing natural tourism objects in Minahasa Regency. The research method used is descriptive qualitative. The findings of this study are that the form and pattern of managing natural tourism objects in Minahasa Regency can be done by combining the principles of local wisdom and special local sense. reflecting the uniqueness of the cultural heritage and the uniqueness of the environment. Natural tourism objects in Bukit Kasih, Lake Tondano and at Kombi Beach in Minahasa Regency have the value of local wisdom and special local sense which can be used as main aspects in managing tourism objects such as the Toar Lumiluut story, the symbol of inter-religious harmony, the legend of Watu Pinabetengan, the legend of the tondano lake, the history of Fort Moraya, the Japanese Heritage Airport Site as well as performances for maengket dance, katrilli and fish farming tours, planting rice around Lake Tondano and the community of grabah craftsmen.